Saline and N-acetylcysteine-based strategies and other approaches to prevent the risk of CA-AKI: a meta-analysis - Lin, I-Chen; Tsai, Wen-Wen; Wu, Vin-Cent; Pan, Heng-Chih; Chuang, Min-Hsiang; Chen, Jui-Yi (Frontiers in Medicine, 2025)
BackgroundWhile hydration is currently the most evidence-supported strategy for preventing contrast-associated acute kidney injury (CA-AKI) in patients undergoing cardiovascular angiography, the potential benefits of combining a saline and N-acetylcysteine (NAC) based strategy with additional pharmacologic interventions remain uncertain.MethodsWe conducted a search for randomized controlled trials (RCTs) in PubMed, Embase, and the Cochrane library from the inception to 26th January 2024. RCTs involving adults undergoing cardiovascular angiography were analyzed, comparing the effects of saline and NAC-based strategies combined with additional agents compared to saline. The primary outcome was the risk of CA-AKI. The comparative effectiveness was visually represented through a network diagram and forest plot, with the treatments ranked by P-score in a league table.ResultsWe included 72 trials with 14,671 patients, 1,843 AKI events, comparing 12 different interventions based on hydration and NAC. The incidence of CA-AKI was 11.74% in the hydration with oral NAC group versus 15.49% in the hydration with saline alone group (odds ratio [OR] 0.78, 95% confidence interval [CI] 0.62–0.97). Compared to individuals with saline alone, the incidence of CA-AKI in the hydration with intravenous NAC group was 10.62% (OR 0.71, 95% CI 0.52–0.99); In hydration with oral NAC and statin group, the incidence of CA-AKI was 8.28% (OR 0.47, 95% CI 0.29–0.77).ConclusionThis network meta-analysis highlights that the combination of hydration with oral or intravenous NAC is more effective than hydration alone in preventing CA-AKI. Additionally, hydration with oral NAC and a statin significantly outperforms hydration with oral NAC alone in preventing CA-AKI.Systematic review registrationCRD42024502497.